An approach to intuitive teaching in the río de la plata (ca.1880-1930) - Alcobre, Mariana (Historia y Memoria de la Educación, 2024)
“Objects lessons” renewed pedagogy worldwide towards the middle of the 19th century. The system was based on learning through observation and sensorial perception of the everyday environment and nature. In our work, we will make a historiographic review of the literature that has studied this method in the Río de la Plata. We will highlight the existence of schoolbooks, consumption patterns, circulation and production of ideas, shared between Argentina and Uruguay. We have articulated this work in two sections: in the first one, we examine the role played by “object lessons” in the consolidation of the Argentine educational system. In the second section, we will analyze the historiography of intuitive teaching in the Río de la Plata, focusing on the classroom, observing the method from all levels of the educational system including teacher training, examining didactic resources such as textbooks, school museums, and didactic plates that were used for the implementation of intuitive teaching. We will also make a survey of the most outstanding personalities who, within education, encouraged intuitive teaching in the region. Through this, we will analyze the reception that “object lessons” had, and the way in which the need for local editions of the method, for teachers and students, was generated; thus we will show how this method became a means to propagate the new educational ideas.